2016
DOI: 10.1039/c6ra20769c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of new phenothiazine-based D–A–π–A dyes for dye-sensitized solar cells

Abstract: We report new D–A–π–A dyes gained by molecular engineering for DSSCs, achieving a highest photoelectric conversion efficiency of 6.35%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Researches have shown that the DSSCs based on metal-complex sensitizers exhibit slightly higher efficiency than those of metal-free organic sensitizers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, the metal-complex sensitizers have limited resources, low molar extinction coefficient and high cost, which limit their industrial applications [ 12 , 14 ]. Studies have revealed that metal-free organic sensitizers provide better performance than metal complexes' sensitizers because of higher molar extinction coefficients, tunable spectral responses, ease of production and availability [ 9 , 10 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Researches have shown that the DSSCs based on metal-complex sensitizers exhibit slightly higher efficiency than those of metal-free organic sensitizers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, the metal-complex sensitizers have limited resources, low molar extinction coefficient and high cost, which limit their industrial applications [ 12 , 14 ]. Studies have revealed that metal-free organic sensitizers provide better performance than metal complexes' sensitizers because of higher molar extinction coefficients, tunable spectral responses, ease of production and availability [ 9 , 10 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many metal-free organic dyes including phenothiazine [ 14 ], carbazoles, coumarin, triarylamines, triphenylamine [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], or phenoxazine [ 24 , 25 , 26 , 27 ] have been designed and synthesized and found to possess promising properties that can enhance photovoltaic performances better than most prominent metal complex dyes. In recent times, phenoxazine has shown preference as an electron-donating moiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkyl and alkoxy chains are known as accessary groups in the architecture of both electron donors and π‐bridges to prohibit the π‐π aggregation of dyes on the TiO 2 surface . Synchronously, the alkoxy chains can play the roles of electron‐donors . As is well known, the typical YD2‐ o ‐C8 dye displays better photovoltaic performance than YD2 dye in their DSC devices owing to its additional octyloxy groups …”
Section: Introductionmentioning
confidence: 99%